Normal tissue doses from MV image‐guided radiation therapy (IGRT) using orthogonal MV and MV‐CBCT. (3rd March 2018) - Li, Yuting; Netherton, Tucker; Nitsch, Paige L.; Balter, Peter A.; Gao, Song; Klopp, Ann H.; Court, Laurence E.
Abstract: Purpose: The aim of this study was to measure and compare the mega‐voltage imaging dose from the Halcyon medical linear accelerator (Varian Medical Systems) with measured imaging doses with the dose calculated by Eclipse treatment planning system. Methods: An anthropomorphic thorax phantom was imaged using all imaging techniques available with the Halcyon linac — MV cone‐beam computed tomography (MV‐CBCT) and orthogonal anterior‐posterior/lateral pairs (MV‐MV), both with high‐quality and low‐dose modes. In total, 54 imaging technique, isocenter position, and field size combinations were evaluated. The imaging doses delivered to 11 points in the phantom (in‐target and extra‐target) were measured using an ion chamber, and compared with the imaging doses calculated using Eclipse. Results: For high‐quality MV‐MV mode, the mean extra‐target doses delivered to the heart, left lung, right lung and spine were 1.18, 1.64, 0.80, and 1.11 cGy per fraction, respectively. The corresponding mean in‐target doses were 3.36, 3.72, 2.61, and 2.69 cGy per fraction, respectively. For MV‐MV technique, the extra‐target imaging dose had greater variation and dependency on imaging field size than did the in‐target dose. Compared to MV‐MV technique, the imaging dose from MV‐CBCT was less sensitive to the location of the organ relative to the treatment field. For high‐quality MV‐CBCT mode, the mean imaging doses to the heart, left lung, right lung, and spine were 8.45, 7.16, 7.19, and 6.51 cGy per fraction, respectively. For both MV‐MV and MV‐CBCT techniques, the low‐dose mode resulted in an imaging dose about half of that in high‐quality mode. Conclusion: The in‐target doses due to MV imaging using the Halcyon ranged from 0.59 to 9.75 cGy, depending on the choice of imaging technique. Extra‐target doses from MV‐MV technique ranged from 0 to 2.54 cGy. The MV imaging dose was accurately calculated by Eclipse, with maximum differences less than 0.5% of a typical treatment dose (assuming a 60 Gy prescription). Therefore, the cumulative imaging and treatment plan dose distribution can be expected to accurately reflect the actual dose.